Analysis on fluid intake and urination behaviors among the elderly in five cities in China: a cross-sectional study - Song, Yongye; Zhang, Yue; Liu, Yan; Zhang, Jianfen; Lu, Junbo; Wang, Xing; Zhang, Na; Ma, Guansheng (Frontiers in Nutrition, 2024)
Background: Fluid intake in the elderly may influence urination behaviors and further influence their health status. This study investigated the behaviors of fluid intake, urination and their relationships among the elderly in China. Methods: Stratified random sampling was used to recruit the elderly participants who met the inclusion criteria from five cities in China. Participants’ total fluid intake (TFI) level was investigated using a validated 7-day 24 h fluid intake questionnaire. Their urination behaviors in real time were also recorded using a validated 7-day 24 h urination behavior record. Results: A total of 524 participants completed the study, including 233 males and 291 females. The average age was 69.7 years. The median daily TFI was 1241 mL, with a frequency of 8.1 times per day. Approximately 73.3% of the participants did not reach the amount of adequate fluid intake (1.7 L for males and 1.5 L for females) recommended in China. Fluid intake in the morning, afternoon, and evening among participants was 594 mL, 305 mL and 342 mL, with a frequency of 3.0 times, 1.7 times, and 2.0 times, respectively. The median urination frequency was 7.4 times per day. The percentage of participants who urinated >7 times during the day was 44.3%. The percentage of participants who urinated ≥1 time at night was 77.5%. Age and BMI were not the main influence factors for fluid intake and urination behaviors. The preliminary analysis showed that higher TFI, plain water intake, dairy products intake, and fluid intake frequency were significantly associated with higher urination frequency (all p < 0.05). Higher fluid intake per time was significantly associated with lower urination frequency (t = -3.562, p < 0.05). Correlations between TFI, fluid intake frequency, fluid intake in night, fluid intake frequency in night and urination at night were also found (all p < 0.05). Conclusions: Fluid intake was inadequate in terms of the elderly participants. Participants with higher fluid intake and frequency in night had a greater incidence of nocturia. Thus, correcting fluid intake behaviors can improve urination behavior and promote health.